Application of distributed optical fiber sensor for monitoring the mechanical performance of a driven pile. (June 2016) - Hong, Cheng-Yu; Zhang, Yi-Fan; Liu, Li-Qiang
Abstract: This paper proposes a special application of Brillouin Optical Time Domain Analysis (BOTDA) sensors for monitoring the mechanical performance of a steel H-pile during driving process in a field in Hong Kong. First, basic calibration and the related installation method of optical fiber sensors (OFS) on pile body were introduced. Second, distributed strain profiles along the H-pile during driving process were successfully obtained from optical fiber sensors. Finally, measured strain distributions of the H-pile subjected to two loading/unloading cycles monitored by OFS were used to interpret field performance of the driven pile. Monitoring results indicate that the vertical load applied on the pile head generated significant compressive deformation, which was however mostly released by the corresponding unloading process. The 1st unloading and 2nd unloading processes released around 66% and 72% of the total compressive pile deformation, respectively. The shear stress levels mobilized between H-pile and surrounding soils were limited after each loading/unloading cycle according to the monitoring results. In addition, loading locations on the driven pile can be clearly identified from strain/stress distribution profiles. It is found from the monitoring study that BOTDA based sensors are more useful than some traditional or other point OFS (such as strain gauges or fiber Bragg grating sensors) to evaluate the average strain distribution of large scale structures.